Comparative Study between Three Analgesic Agents for the Pain Management during Extracorporeal Shock Wave Lithotripsy - Liu, Jianjun; Zang, Yun-jiang (Urology Journal, 2013)
Purpose: To compare the clinical efficacy between locally applied diclofenac diethylamine gel, EMLA cream and systemically given diclofenac sodium for the pain relief during extracorporeal shock wave lithotripsy (SWL) using Dornier Delta Compact Lithotripter. Material and Methods: One hundred five patients with renal stones were randomly divided in to 3 groups. Group A was given intramuscular diclofenac sodium (1 mg/kg), 45 minutes before the procedure. In group B, 10 gm of eutectic mixture of local anesthetic (EMLA) cream and in group C, 15 gm of diclofenac diethylamine gel was applied locally 45 minutes before the procedure. Ten-score linear and visual analogue scale (VAS) was used to assess the severity of pain during the procedure. Analysis of variance (ANOVA) test was used to compare various parameters and analyzed statistically. Results: All the three groups were not statistically different with respect to age, weight, stone size, number of shock wave delivered and maximum voltage used (P > .05). The mean pain score in group A was 4.48, in group B was 3.60 and in group C was 3.95, which were not significantly different (P = 1.34). Complication like skin lesion was found only in injection diclofenac sodium group whereas cold sensation at the local site was typically found in diclofenac diethylamine gel group. Conclusion: Although not statistically significant, the mean pain score in locally applied analgesic agents (EMLA and diclofenac diethylamine gel) is lower as compared to intramuscularly given diclofenac sodium. Among these two locally acting drugs, diclofenac diethylamine gel is an equally effective alternative to EMLA.